Arkangel [compact disc, unabridged] - Rollins, James, 1961- (Rollins, James, 1961- Sigma Force novel., 2024)
The execution of a Vatican archivist within the shadow of the Kremlin exposes a conspiracy going back three centuries, to the bloody era of the Russian Tsars. Facing enemies on all sides, it will be up to Sigma Force to unravel a mystery going back millennia and uncover the truth about a lost civilization and an arcane treasure that could save the planet, or destroy it.